Neutrophil–lymphocyte ratio – a simple, accessible measure of inflammation, morbidity and prognosis in psychiatric disorders?. (August 2020) - Zulfic, Zlatan; Weickert, Cynthia Shannon; Weickert, Thomas W; Liu, Dennis; Myles, Nicholas; Galletly, Cherrie
Objective: A narrative review to describe the utility of the neutrophil-lymphocyte ratio (NLR) as an inflammatory marker in psychiatric and non-psychiatric disorders and to discuss the potential role of NLR in psychiatric research. Conclusions: NLR is inexpensive and readily available using division of two measures obtained on routine blood testing. NLR is elevated in a number of psychiatric disorders. It can predict morbidity and mortality in a wide range of non-psychiatric conditions, but this has not been confirmed in psychiatric conditions. It can be calculated in large, pre-existing datasets to investigate clinical correlates of inflammatory processes. NLR may have a future role in identifying patients with an inflammatory phenotype who could benefit from adjunctive anti-inflammatory medications.